PRESTASI PENGEMUDI TRUK ANGKUTAN DI SUATU PENGUSAHAAN HUTAN DI KALIMANTAN BARAT - Dulsalam Dulsalam; Sukanda Sukanda (Jurnal Penelitian Hasil Hutan, 1990)
An investigation on  logging truck  drivers performances was carried out at a  logging company  in West Kalimantan in 1988. Seven  logging truck  drivers were observed  using seven Nissan TZ 50 semi-trailer  logging trucks  (made in 1979). The  purpose of  this  investigation is to  find  out logging truck  drivers performances necessary for logging companies to plan their employment in hauling activity. For  this purpose, the  investigation   was done through work  time study. The investigation comes  to  the  following conclusions   : PT  Duadja  II  employs   several  logging  truck  drivers  having  various skills. Nissan  TZ  50 semi-trailer logging trucks are used  to  transport  logs from the forest  to  log pond.Average  performances of  A, B, C, D, E, F, and  G logging  truck  drivers  were 765.79,   695.85, 652.56, 843.31, 745.07, 709.20,  and  759.18 m3km/hour, respectively.The performances  among  logging truck  drivers  were  significantly different due  to  the  differences in load volumes and logging truck speeds as well as drivers' age and education  levels.